2009
DOI: 10.1094/cchem-86-5-0499
|View full text |Cite
|
Sign up to set email alerts
|

Tocopherol and Tocotrienol Content in Commercial Wheat Mill Streams

Abstract: The content of tocopherols and tocotrienols, collectively known as vitamin E (tocols), was determined in fractions of roller‐milled wheat grains. The results showed that vitamin E components are present in all major flour fractions of wheat, but that the vitamin E content and composition differed significantly between fractions. The total content of vitamin E, calculated as alpha‐tocopherol equivalents, changed from 16.1 mg α‐TE/g in wheat grain to 12.2 mg α‐TE/g in roller‐milled wheat flour. The germ fraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 25 publications
0
19
1
2
Order By: Relevance
“…Within the grain, tocopherols are primarily located in the germ and aleurone tissue, the metabolically active parts of grain (Engelsten & Hansen, 2009). Therefore, higher content was found in wholegrain than in refined crackers.…”
Section: Tocopherols Contentmentioning
confidence: 99%
“…Within the grain, tocopherols are primarily located in the germ and aleurone tissue, the metabolically active parts of grain (Engelsten & Hansen, 2009). Therefore, higher content was found in wholegrain than in refined crackers.…”
Section: Tocopherols Contentmentioning
confidence: 99%
“…Vitamin E, a major biological antioxidant, is mainly provided by cereal grains. Engelsen and Hansen (2009) showed that tocopherols are primarily located in the germ fraction, but are also present in the fraction of fine bran. Several factors can influence tocopherol stability, including temperature, light, concentration and substrate.…”
Section: Introductionmentioning
confidence: 99%
“…Also, in another study it was observed that α-and β-T were predominant in the germ fraction of einkorn wheat while α-and β-T3 levels were highest in its bran fraction (Hidalgo & Brandolini, 2008). In a study by Engelsen and Hansen (2009), the content of tocopherols and tocotrienols varied depending on the wheat fractions. The content of tocotrienols was distributed uniformly in the wheat grain with the highest content in the bran fractions.…”
Section: Vitamin E Content Of Korean Whole Wheat Cultivarsmentioning
confidence: 91%